Interaction Between Transcranial Random Noise Stimulation and Observation-Execution Matching Activity Promotes Motor Cortex Excitability - Qi, Fengxue; Nitsche, Michael A.; Zschorlich, Volker R. (Frontiers in Neuroscience, 2019)
Pathways of the human mirror neuron system are activated during both, action observation and action execution, including lateralized activation of respective areas, as shown by observed right-or left-hand actions. Here, we investigated whether execution-dependent motor cortex excitability is affected by prior interaction between transcranial random noise stimulation (tRNS) and action observation. Sham or real tRNS (1 mA) was applied for 10-minute over the left primary motor cortex during action observation. In the main experiments, participants received sham or real tRNS while they watched a video showing repeated tapping tasks, involving either the right-hand (experiment 1, congruent action observation), or a mirror-reversed video showing the same performance (experiment 2), followed by action execution of the right-hand. In control experiments 1-3, participants received real tRNS while observing a perceptual sequence, watching a landscape picture, or observing the left-hand performing the action (the sequence was identical to experiment 1), followed by action execution of the right-hand. In control experiment 4, participants received real tRNS during congruent action observation, and then took 6-min rest. Motor-evoked potentials (MEP) were recorded before action observation, a perceptual sequence or a landscape picture, immediately after, and after action execution, or an interval of 6-min, dependent on the respective experimental condition. MEPs in the right first dorsal interosseous muscle increased significantly after real tRNS combined with congruent action observation, and after action execution compared to the sham session in experiment 1 and control experiments. We conclude that prior interaction between real tRNS and action observation of mirror-matched movements modulates subsequent execution-dependent motor cortex excitability.